Implementation of Accrual Base Accounting to Improve Accountability: A Case of Gambia - Conteh, Saikou; Hamidah, Hamidah (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2021)
Public sector changes in Gambia started within the 1980s with the essential objective of moving forward the adequacy, effectiveness, and straightforwardness of governmental operational and financial administration. This paper was executed by adopting qualitative research method to obtain it findings. This paper points to look at the opportunities and accountability by the Gambian public sector in executing accrual-based accounting. A survey of past writing in this range appeared that accrual-based accounting improves decision-making processes, advances way better financial administration, and enhances public accountability. Be that as it may, the move handle between these two accounting strategies isn't without challenges. Human resources competency, software and technology capability, accounting policies, and measures appropriateness are recognized as major challenges within the usage effort. These challenges should be taken into thought carefully by the government in order to guarantee effective movement towards accrual-based accounting.